2017
DOI: 10.1177/0733464817732511
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Late Life Patients: Mixed-Methods Evaluation of a Whole-Person Approach for Patients With Chronic Illnesses

Abstract: Quality of life (QOL) for patients with serious illness in late life is important for patients and policy makers and has implications for improved care delivery. This mixed-methods evaluation examined the effectiveness of a new whole-person approach to late life care-the LifeCourse-which provides patients with ongoing, across-setting assistance from lay health care workers, supported by a clinical team. We investigated whether participation in LifeCourse improves QOL for intervention patients, compared with us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For example, the Aging Brain Care model has shown that collaborative care incorporating lay interventionists ("care coordinator assistants") may improve clinical outcomes in older adults with dementia. 50 Our search strategy also identified several relevant studies that were excluded based on age during screening (due to participants under age 60), including the LifeCourse model, which incorporates lay "care guides" to improve quality of life in seriously ill older adults, 51 and the IMPaCT CHW model, which has demonstrated improved health outcomes in adults with multimorbidity. 22,23 Our review did include several studies with socially vulnerable participants, but this was not specified in our eligibility criteria for complexity.…”
Section: Citationmentioning
confidence: 99%
“…For example, the Aging Brain Care model has shown that collaborative care incorporating lay interventionists ("care coordinator assistants") may improve clinical outcomes in older adults with dementia. 50 Our search strategy also identified several relevant studies that were excluded based on age during screening (due to participants under age 60), including the LifeCourse model, which incorporates lay "care guides" to improve quality of life in seriously ill older adults, 51 and the IMPaCT CHW model, which has demonstrated improved health outcomes in adults with multimorbidity. 22,23 Our review did include several studies with socially vulnerable participants, but this was not specified in our eligibility criteria for complexity.…”
Section: Citationmentioning
confidence: 99%
“…This indicates that they had some understanding of palliative care, as it involves treating the patient as a whole person (Riordan, Briscoe, Kamal, Jones, & Webb, ). Furthermore, attending to end‐of‐life patients' spiritual needs could help improve their quality of life (Brady, ; Shippee et al, ). Nurses also placed importance on completing unfinished business, preparing for death, and having loved ones around when the patients needed them, which is consistent with the findings of several prior studies (Endacott et al, ; Meier et al, ; Steinhauser et al, ).…”
Section: Discussionmentioning
confidence: 99%